MODAL AND HARMONIC RESPONSE CHARACTERISTICS ANALYSIS OF HIGH RELIABLE SCROLL COMPRESSOR FOR NEW ENERGY VEHICLES - CHEN JiJie; ZHANG LiYong; SHEN DuoBiao; WANG GuanBo; YU FeiPeng; GUAN HongJie; JIANG YeHu; TANG Juan; LI TongJie; WANG Juan; JIANG PanFei; LI Gen; et al. (Jixie qiangdu)
The thermal management system of new energy vehicles directly affects the overall vehicle performance,placing stringent demands on the performance and reliability of the scroll compressor for air conditioning,with particular emphasis on the mass imbalance response of the scroll compressor drive shaft for its performance and service life.For a certain type of scroll compressor drive system with a design speed of 0~7000 r/min,based on the distributed mass model,the intrinsic characteristics of the shaft system and the unbalance response at different speeds were analysed by using the modal method.Considering the robustness of the simulation speed setting,the rotor system was set at 0~7000 r/min,and the first six orders of the intrinsic frequency,vibration mode and the positive vortex criticality were obtained.The first six orders of intrinsic frequencies,vibration mode and critical speeds of positive eddy currents were obtained for the rotor system at 15452 r/min and 32839 r/min,and the deformations and stresses of the spindle eccentric pins,the balancing block and the tail section were analyzed by the harmonic response analysis under the excitation of the gas loads to obtain the variation of the frequencies.Finally,the prototype was experimented,and the measured acceleration time-domain and frequency-domain response curves were obtained.The results show that the scroll compressor does not reach the critical speed under the design speed of 0~7000 r/min;the unbalanced vibration at 271.96 Hz and 517.01 Hz and its side frequency has a greater impact on the rotor,which is consistent with the results in the harmonic response analysis.The study provides a reference for the vibration finite element analysis and structural optimization of the scroll compressor.